Potencial de plantas medicinais no tratamento da hipertensão arterial: Allium sativum - (:unkn) unknown (ICET - Instituto de Ciências Exatas e Tecnologia (Itacoatiara), 2024)
The incidence of hypertension is increasing significantly on a global scale and is considered the main cause of heart disease. Despite the wide availability of antihypertensive drugs, they have many side effects that hinder or reduce adherence to pharmacological treatment. Current studies reveal that medicinal plants, such as Allium sativum, contain important properties that may be promising for reducing blood pressure. A literature review was carried out using the SciELO (Scientific Electronic Library Online), Medline (Pubmed) and Scopus (Elsevier) databases, from 2014 to 2024. The following keywords were used as a search basis: phytotherapy, medicinal plants, antihypertensives, Allium sativum. The search was limited to original articles in English published between 2014 and 2024. The available evidence revealed that garlic (Allium sativum) reduces blood pressure parameters. Based on animal and human studies, it has been reported that the mechanisms of antihypertensive effect of Allium sativum are due to the presence of many active sulfur molecules that have been shown to stimulate endothelial relaxing factors, leading to a reduction in blood pressure. The review of the current literature showed studies that confirmed that A. sativum may be a potential antihypertensive agent. Some limitations should be considered, such as the variability in the results of clinical studies, indicating that further research is needed to standardize dosages, identify possible long-term side effects, and fully explore its therapeutic potential.
Keywords: Hipertensão arterial; Allium sativum; Plantas medicinais; CIENCIAS DA SAUDE: FARMACIA; .; .